Crown discoloration due to the use of triple antibiotic paste as an endodontic intra-canal medicament - Manuel Sebastian Thomas (Wolters Kluwer Medknow Publications, 2014)
The use of triple antibiotic paste (TAP) (mixture of ciprofloxacin, metronidazole and minocycline) as an intra-canal medicament have shown very encouraging results particularly in non-vital immature teeth associated with periradicular lesions. Hence, before opting for a surgical approach, a non-surgical approach can be thought of with extended use of TAP as intra-canal medicament, especially in patients who are phobic to invasive procedures. On the flip side, the use of TAP has few side-effects, of which one is the discoloration it can cause due to the presence of minocycline in the mix. The purpose of this article is to presents a case of coronal discoloration due to the use of TAP as an endodontic intra-canal medicament.